Implementation of collaborative teamwork learning model to improve basketball passing learning outcomes - I Gede Yogi Wijendra; Made Agus Wijaya; Kadek Yogi Parta Lesmana (Sriwijaya Journal of Sport, 2024)
Background Problems: In the learning process at SMA Negeri 2 Singaraj, researchers found problems in the learning process in the basketball game material, especially in the basic techniques of passing chest passes and bounce passes, which had a low average below the minimum completion criteria. Research Objectives: This research aims to improve learning outcomes in basketball, the basic technique of passing chest passes and bounce passes through the Collaborative Teamwork Learning model for class XI A1 students at State Senior High School 2 Singaraja. Methods: Classroom action research (CAR) is used. This classroom action research (CAR) uses teachers as researchers and consists of 2 cycles. The subjects of this research were students in class XI A1 of State Senior High School 2 Singaraja, with 40 people consisting of 20 male students and 20 female students. The research instrument is a description test for the knowledge aspect and performance for the skills aspect. Data analysis uses qualitative and quantitative descriptive analysis. Results: The results of the research showed an increase, namely learning completeness in the knowledge aspect in cycle I, which was (85.5%), in cycle II it increased to (92.5%). Furthermore, learning completeness in the skills aspect in cycle I was (87.5%) in cycle II (92.5%). Conclusion: Based on data analysis and discussion, it is concluded that the collaborative teamwork learning model can improve PJOK learning outcomes in basketball passing material for class XI A1 students at SMA Negeri 2 Singaraja for the 2023/2024 academic year. Suggestions for PJOK teachers to be able to implement the Collaborative Teamwork Learning model in other learning materials that are more interesting and effective. The research implies that the Collaborative Teamwork Learning model is proven to be able to improve student learning outcomes.